Societal perception on the government role in governing development and ethnic relations in Malaysia - Ismail, Mohd Mahadee; Mohd Noor, Mansor; Abdullah, Azlina; Hassan, Nor Azlili; Idris, Fazilah; Muslim, Nazri; Husain, Ab. Bassit (Human Resource Management Academic Research Society, 2018)
This article discusses the perception of the society on the role played by the government in implementing the governance responsibilities of the country's development, particularly in the context of managing and organizing social differences in the Malaysian society. The diversity in Malaysia is not only generates a dynamic social composition, but has brought significant challenges to the government in managing the country's governance more effectively. In addition, the civic consciousness among the current Malaysian society has claimed various demands such as for a fair, transparent and equitable government, society’s interests, as well as generating good economic development and sustaining social well-being in society. This study explores the perceptions of the community towards the role of the government in the context of economic governance, holistic development, community management, establishment of government services, program implementation, political, media, criminal governance and social problems. This study indicates each ethnic group presented different feedbacks in every aspect. However, there is no negative dimension that shows the failure of the government in implementing a good governance, but still need some improvement based on the perception of the respondents. Implementation of development, governance is important in the context of promoting good ethnic relations between the diversity of societies in Malaysia. Thus, good ethnic relations are the substance for the formation of social cohesion and the continued assurance of national stability in Malaysia.